PENGEMBANGAN MODUL INKUIRI BERBASIS SCIENTIFIC REASONING ABILITY PADA MATERI ZAT ADITIF - Wahyuningsih, Maya Eka; Hadi, Wiwin Puspita; Tamam, Badrud; Astid Putera, Dwi Bagus Rendy; Sutarja, Maria Chandra (Natural Science Education Research, 2023)
The purpose of this study are to determine the feasibility, readability, and student responsses to the inquiry module based on scientific reasoning ability in additive material. The type of this study is development research, where the study uses the ADDIE development model. The research design used in this study was purposive sampling. The research was conducted at AL-Hikam Burneh Middle School, in the class VIII-A with samples of  36 students. The research was conducted in January 2023. The result of this study indicates that the average validity results for the feasibility of the module are 90.60% wich categorized as a very valid category and the reliability value is 94.78% wich categorized as a very reliable category. The average percentage of all aspects of student readability has a value of 81.89% categorized in the very good category and the average percentage of all aspects of student responsse has a value of 86.30% categorized in the very good category. The inquiry module based on scientific reasoning ability on material additives is declared feasible to use.